Thermal comfort control in smart home environment based on Cyber- Physical System - Lim, Wilson Wei Chien (Universiti Malaysia Sarawak (UNIMAS), 2017)
CPS is an integration of physical dynamics and computational systems, so they commonly combine both discrete and continuous dynamics. Therefore, modelling of cyber and physical processes is also known as hybrid system modelling.CPS-based hybrid temperature control system (HTC) in smart home is concerned with sensing and timely control the multiple actuators to maintain a desired temperature with the optimized cost through the communication network. The indoor temperature fluctuated by internal and external heat loads are always sensed by the sensors. With the closed-loop interactions, the indoor temperature is feedback to the controller. Then, the controller with the decision-making algorithm decides the control actions which is send to actuators or device controller via the communication network to change the state of the physical world and to satisfy the specified goal. In this project, we will be designing and implementing a thermal comfort control CPS by using MATLAB/Simulink. We will then optimize it as the CPS is built with multi actuators to achieve the lowest energy consumption at any given condition while maintain the building in the desired temperature.